Effect of Cilostazol on Soluble Adhesion Molecules and Platelet-derived Microparticles in Patients with Diabetes - Nomura, Shosaku; Shouzu, Akira; Omoto, Seitaro; Hayakawa, Takashi; Kagawa, Hideo; Nishikawa, Mitsushige; Inada, Mitsuo; Fujimura, Yoshihiro; Ikeda, Yasuo; Fukuhara, Shirou (Thrombosis and Haemostasis, 1998)
We evaluated the plasma concentrations of soluble adhesion molecules and platelet-derived microparticles (PMP) in patients with non-insulin dependent diabetes mellitus (NIDDM) and studied the effect of cilostazol on PMP generation. There were differences in the levels of soluble adhesion molecules between NIDDM patients (N = 43) and the control subjects (N = 30) (soluble thrombomodulin: 11.5 ± 5.3 vs. 7.0 ± 1.2 TU/ml, p<0.0001; soluble vascular cell adhesion molecule-1: 708 ± 203 vs. 492 ± 113 ng/dl, p<0.0001; soluble intercellular cell adhesion molecules-1: 274 ± 65 vs. 206 ± 48 ng/dl, p<0.0001; soluble P-selectin: 194 ± 85 vs. 125 ± 43 ng/dl, p<0.0001). There were also differences in the levels of PMP and platelet activation markers between NIDDM patients and the controls (PMP: 943 ± 504 vs. 488 ± 219/10 4 plt, p<0.0001; platelet CD62P: 9.2 ± 4.6 vs. 4.4 ± 4.3%, p<0.001; platelet CD63: 10.2 ± 4.5 vs. 4.5 ± 3.3%, p<0.0001; platelet annexin V: 9.1 ± 3.9 vs. 5.3 ± 3.8%, p<0.001). To study the release of PMP into plasma, a modified cone-and-plate viscometer was used. Increased release of PMP from platelets was observed in diabetic plasma compared to normal plasma under high shear stress conditions (2,672 ± 645 vs. 1,498 ± 386/104 plt, p<0.05). Therefore, one cause of PMP elevation in NIDDM may be high shear stress. The levels of PMP, activated platelets, and soluble adhesion molecules all decreased significantly after treatment with cilostazol. These results suggest that cilostazol may be useful for the inhibition of both PMP-dependent and -independent vascular damage in NIDDM.